Household responses to poverty and vulnerability. Vol. 3, Confronting crisis in Commonwealth, metro Manila, Philippines - Moser, Caroline O. N., 1944- 1944- (The World Bank, 1997)
This study explored how poor households respond to changes in economic circumstances and labor market conditions, i.e. how the impact has been felt on the ground." It looked at how poor households adjust to a deteriorating situation, what strategies they adopt to limit the impact of shocks and generate additional resources, and what constraints impede their actions. This case study presents the main findings from the community of Commonwealth in Metro Manila (Philippines); other volumes focus on Chawama, in Lusaka, Zambia; Cisne Dos, in Guayaquil, Ecuador; and Angyalfold, in Budapest, Hungary. The results show that the four communities cope in remarkably similar (and dissimilar) ways. Three features distinguish this study from other poverty studies:a micro-level approach combining households and communities as the main units of analysis, an unusually long period of observation for some communities and households, and a comparative framework offering four cases with very different economic levels and institutional contexts. The study used income measures, recognizing its multifaceted nature, as well as socio-psychological factors, incorporated in the concept of "vulnerability," the insecurity of the well-being of individuals, households, or communities in the face of a changing environment. Analyzing this concept involves identifying not only the threat, but also the "resilience" in exploiting opportunities and in resisting or recovering from the negative effects of the changing environment. As in the other research communities, the labor market was a major source of vulnerability in Commonwealth. Households responded to declining income by mobilizing the labor of additional household members. Access to both labor and human capital was central to households' capacity to endure economic change without irreversibly damaging their asset base.